Non‐destructive biomass estimation of Oecophylla smaragdina colonies: a model species for the ecological impact of ants. Issue 5 (21st March 2015) - Pinkalski, Christian; Damgaard, Christian; Jensen, Karl‐Martin V.; Gislum, Rene; Peng, Renkang; Offenberg, Joachim; Dytham, Calvin; Brady, Seán
Abstract In most ecosystems, ants are a dominant part of the arthropod community. A thorough understanding of their ecological impact, however, has been hampered by limited availability of data on ant abundance. Therefore, we developed a method allowing quick and non‐destructive estimates of the biomass of Oecophylla smaragdina colonies in mango plantations. The method was based on assessments of ant nest volume in relation to ant trail density and biomass content in relation to nest volume. The relationships between these variables were modelled using Bayesian latent variable models. The resulting models predicted ant biomass from ant trail activity with a maximum uncertainty of approximately 75% of the predicted value. Five O. smaragdina colonies assessed in a mango plantation, ranged in size from 0.67 to 2.98 kg total ant biomass (fresh wt) and 84.578–376.635 workers for the smallest and largest colony respectively. Correspondingly, the density of ants in the plantation was 254 workers m−2 and a total biomass of 2.0 g ant fresh wt m−2. With this proposed method, estimates of O. smaragdina abundance can be obtained non‐destructively with a minimum of workload and it enables the scaling up of physiological experiments on per capita rates. Thus, O. smaragdina can serve as a model species providing information on the impact of ants in tropical ecosystems.